Community Economic Resilience Through Organic Waste Management in Jatisura, Indramayu Regency, West Java - Sufyati HS; Tati Handayani; Faizi Faizi; Anggi Angga Resti; Abdul Husen Zaelani (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
To realize an increase in people's living standards, and to overcome poverty and unemployment, it is necessary to collaborate with the government, universities and the community. The Regional Government of Indramayu Regency in collaboration with the Jakarta Veterans National Development University collaborates in research and community service. In this case, the selected village is Jatisura village as the centre for implementing community service activities Jatisura Village is a mango-producing village in Indramayu which has problems with waste management. Garbage as household, market and industrial waste has become a national problem because it can pollute the environment and public health if no one manages it professionally. The target of this activity is organic waste management. The purpose of this activity is to make waste a resource that has economic value that can increase the income of the Jatisura village community. The implementation method carried out consists of several stages. Planning and preparation stage; Partner analysis stage; Stages of implementation and assistance; Monitoring and evaluation stage. The results of this activity indicate that the average participant understands the process of managing organic waste into Local Microorganisms (MOL) products and using it as a substitute for chemical fertilizers. Service activities are not only for the benefit of lecturers at universities but for the benefit of the local village community and generally villages in Indramayu Regency